Water quality assessment of hot springs and its discharges into the tributaries fed into the Bogotá river - Sánchez Londoño, Yuly Andrea (Centro de Estudios Ambientales, 2023)
The hot springs are used for recreational, therapeutic, and medicinal purposes. Due to their mineralization and water temperature, they convey a feeling of well-being that makes them a great tourist attraction. However, bathers do not know the quality of the waters, so it is necessary to identify the possible risks to which bathers are exposed. In Colombia, hot springs are not disinfected before human use and their wastewater is discharged directly into rivers, nor is it customary to carry out monthly monitoring of their water quality. For this reason, it is important in Colombia to advance in the investigation of risk indicators for human health and the quality of aquatic ecosystems. In this thesis, two types of hot springs that discharge to tributary water sources of the Bogotá river were studied. Its waters were monitored for six months to determine the physical, chemical, and microbiological quality of the water and to assess its compliance with drinking water, swimming pool, hot spring, and wastewater discharge standards. The results showed that each hot spring had its own unique water characteristics, with hot spring 1 being bicarbonate and hot spring 2 being ferruginous. The values from the heavy metals analyzed (arsenic (As), chromium (Cr), mercury (Hg), lead (Pb), aluminum (Al), copper (Cu), iron (Fe), magnesium (Mg), manganese (Mn), nickel (Ni), zinc (Zn), strontium (Sr), and calcium (Ca)) in the samples from hot springs 1 and 2 were compared with regulations for drinking water and swimming pools. These values were within the limits established by the regulation, with the exception of the hot spring 2 featuring high iron values, which becomes more of a water aesthetic problem. Parameter analysis revealed that hot spring 1 had high conductivities and pH values higher than 7.0, while hot spring 2 had lower conductivities and pH values between 6.0 and 7.7. Dissolved oxygen levels in both hot springs remained within acceptable ranges. Concentrations of heavy metals in the samples were found to be within the limits set by drinking water and swimming pool standards, except for the high iron values in hot spring 2, which posed mainly an aesthetic concern. Hot spring 2 exhibited high turbidity and color values due to the ferruginous properties of the water. Oil and fats were not quantifiable in any hot spring. Hot spring 1 presented calcium carbonate values above the regulatory limits for drinking water and swimming pools. The results also indicated the presence of fecal coliforms (E. coli), total coliforms, Enterococci, L. pneumophila, P. aeruginosa, molds, and yeasts in all samples, exceeding the permissible limits. The use of UV for disinfection of hot springs without the use of chemicals has shown promising results. The tests conducted in the laboratory demonstrated high removal efficiencies, reaching up to 99.9% for bacteria such as E. coli. This method preserves the physical and chemical properties of the water, ensuring that it remains in its natural state.However, it is important to note that UV disinfection can be costly, particularly for smaller hot springs. Overall, this study provides valuable insights into the water quality of the analyzed hot springs and highlights the need for appropriate regulations and treatment measures to ensure the safety and compliance of hot springs with respect to human health and environmental protection. Further research and implementation of effective management strategies are necessary to address the specific water characteristics and contamination issues associated with hot springs in order to safeguard public health and preserve the integrity of aquatic ecosystems.
Keywords: Calidad del agua -- Aguas termales -- Río, Bogotá; Aguas termales -- Bicarbonato -- Río, Bogotá; Aguas termales -- Ferruginoso -- Río, Bogotá